Production Budget for Tomatoes in Southwest Florida - John VanSickle; Scott Smith; Eugene McAvoy (EDIS)
FE818, a 5-page fact sheet by John VanSickle, Scott Smith, and Eugene McAvoy, provides producers with a brief overview of the tomato industry and production practices in southwest Florida, with a per-acre composite budget for a representative grower. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.